Analysis of Clinical Characteristics of 35 Cases of Pulmonary Sclerosing Pneumocytoma - Liu, Xiaojing; Huang, Zhihao; Zhang, Jianyong (Zhongguo fei ai za zhi, 2020)
Pulmonary sclerosing pneumocytoma (PSP) is rare benign lung tumor which usually develops in middle-aged women without typical clinical and imaging findings. PSP consists of two basic cell types (surface cubic epithelial cells and round mesenchymal cells) and four histological types (hemorrhagic, sclerotic, solid and papillary). It grows slowly, but it can metastasize to distant organs. The pathology before surgery is easily misdiagnosed. This study aims to improve clinicians' understanding of PSP by discussing the clinical characteristics of the disease. This represents a retrospective study of thirty-five patients diagnosed with pulmonary sclerosing pneumocytoma by pathological examination from January 2011 to December 2019. A total of 35 patients in this study, 12 cases were male and 23 cases were female, the average age is 51 years old. 7 cases were discovered accidentally by physical examination or routine chest computed tomography (CT), and 28 cases were found due to symptoms such as cough, sputum, hemop